Höhentraining: Sinn, Unsinn, Trends = High altitude training : benefits, problems, trends - Friedmann-Bette, Birgit; Bärtsch, Peter (Der Orthopäde, 1997)
Athletes who need high endurance capacity often use training at moderately high altitude (1500-3000 m) to improve oxygen delivery and utilization because of a hypoxia-induced increase of the red blood cell volume and adaptations at the muscular level. As maximal heart rates decrease at high altitude and plasma lactate levels for a given workload change during prolonged exposure to high altitude, it can be difficult to control and adapt the intensity and duration of the work-outs. Furthermore, maximal performance capacity decreases and therefore training intensity at high altitude is usually reduced compared to training at sea level. To avoid these disadvantages at high altitude a concept of living at moderately high altitude and training at lower elevations, termed ”live high - train low” evolved, opposing the conventional concept of ”live high - train high”. A third option using a hypobaric chamber (”live low - train low”) is hardly used anymore for training athletes. Studies on the effects of conventional high-altitude training for the improvement of athletic performance often lack a rigorous controlled design and yield controversial results. Regarding the new concept of ”live high - train low” there is only one controlled study on college athletes and it shows a minor advantage of this new approach compared to conventional high-altitude training. However, training concepts are especially important for elite competitive athletes, and controlled studies with such individuals are very difficult to perform. Therefore, it appears that today we cannot answer the question of whether altitude-specific physiologic factors or non-altitude-related benefits of training camps account for the success of individual athletes.
Abstract in englischer Sprache
Gesehen am 29.01.2024